The extent of the legality of contracts in the case of convergence with the contracts of the insurance company - AL-qudah, Musa (Jordan Journal of Islamic Studies, 2023)
The study aimed to demonstrate The Availability Of Sharia Controls For Meeting Contracts In The Case Of A Loan With No Interest Meeting With The Contracts Governing Relationship Of The Islamic Insurance Company With The Policy Holder , AsAn Applied Study On The (AAOIFI) standard -26., and it was found that the loan offered by the Islamic Insurance Company for the policy holders when it is unable On fulfilling his obligations, he meets, at least, with the policy holders contract for the insurance company to manage the insurance business for a fee. This meeting enters the circle of Sharia prohibition of a predecessor and sale meeting, In view of the absence of specific criteria for controlling the amount of what the company charges for its management or investment on the one hand and on the other hand the absence of controls to determine the expenses of the account holder of non-technical documents that he or the account of the insurance company incurs, The study recommends the necessity of setting the necessary controls for the above, out of the circle of Sharia prohibition.